Surgical interventions for vitiligo: an evidence‐based review. (4th October 2013) - Mulekar, S.V.; Isedeh, P.
Abstract : What's already known about this topic? Surgical interventions are indicated in the setting of stable vitiligo, unresponsive to conventional therapies. Surgical interventions includes tissue and cellular grafting techniques. What does this study add? This is an evidence‐based review comparing the various surgical interventions for vitiligo. It underscores the need for more randomized clinical trials evaluating the safety and efficacy of surgical interventions for vitiligo. It highlights the need for global standardization in the assessment of repigmentation using objective rather than subjective criteria. Summary: Background: Vitiligo is a disfiguring disease, characterized frequently by the presence of de‐pigmented macules and/or patches. Traditional therapies are essentially medical and are most preferred by dermatologists. Surgical therapies, however, are amongst the most effective interventions for vitiligo but are limited by their invasive nature, as well as the training and expertise needed to perform specific procedures. Objectives: To assess the evidence for the effectiveness, safety and applicability of the various surgical methods in the treatment of vitiligo. Methods: For this systematic review of vitiligo surgical therapies, our searches included: PubMed, MEDLINE and Cochrane databases. Results: We reviewed research studies reporting on split thickness skin grafts (STSG), punch/mini‐graft, blister roof grafting, cultured and non‐cultured cellular transplantation (MKTP). While all methods vary in their repigmentation outcomes, STSG is found to have the highest repigmentation success rate. Overall, post‐operative complications included milia, scarring, cobblestone appearance or hyperpigmentation of treated areas. Conclusion: This review highlights the need for more randomized controlled trials in this field, underpinned by a more standardized objective approach to the assessment of repigmentation following surgical interventions.